2012
DOI: 10.1097/mnh.0b013e3283546ee0
|View full text |Cite
|
Sign up to set email alerts
|

Management of mineral and bone disorder after kidney transplantation

Abstract: Purpose of review Mineral and bone disorders (MBD), inherent complications of moderate and advanced chronic kidney disease (CKD), occur frequently in kidney transplant recipients. However, much confusion exists about clinical application of diagnostic tools and preventive or treatment strategies to correct bone loss or mineral disarrays in transplanted patients. We have reviewed the recent evidence about prevalence and consequences of MBD in kidney transplant recipients and examined diagnostic, preventive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 131 publications
(139 reference statements)
1
68
0
12
Order By: Relevance
“…In a study by Kasiske et al (26) in the 1990s, no relationship was observed between Framingham risk factors, including smoking, hypertension, and hyperlipidemia, and the risk of myocardial infarction, cardiac death, and coronary interventions in recipients of renal transplants (26). Among nonclassic risk factors, CRP (9) and biomarkers of CKD-MBD (10) undergo dramatic changes after transplantation, and FGF23 and 1,25(OH) 2 vitamin levels approach the normal range in most patients, whereas serum PTH often remains mildly to moderately elevated (27). Numerous low-powered cross-sectional ultrasound studies of carotid arteries have been performed in patients with renal transplants (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kasiske et al (26) in the 1990s, no relationship was observed between Framingham risk factors, including smoking, hypertension, and hyperlipidemia, and the risk of myocardial infarction, cardiac death, and coronary interventions in recipients of renal transplants (26). Among nonclassic risk factors, CRP (9) and biomarkers of CKD-MBD (10) undergo dramatic changes after transplantation, and FGF23 and 1,25(OH) 2 vitamin levels approach the normal range in most patients, whereas serum PTH often remains mildly to moderately elevated (27). Numerous low-powered cross-sectional ultrasound studies of carotid arteries have been performed in patients with renal transplants (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Интересна и установленная нами достаточно тесная ассоци ация сывороточных концентраций магния и ПТГ. Получены доказательства того, что гипомагниемия у реципиентов связана с более быстрыми темпами снижения функции почечного трансплантата, и сле довательно, развития ГПТ [1,41].…”
Section: гипомагниемияunclassified
“…Кроме того, в посттрансплан DOI: 10.15825/1995-1191-2017-1-111-121 трАНСПлАНтАЦиЯ ПОчКи и КОСтНАЯ БОлеЗНь: ФАКтОрЫ риСКА рАЗВитиЯ, диАГНОСтиКА тационном периоде появляются новые причины, участвующие в развитии костной болезни. Интерес специалистов многих стран к данной проблеме ве лик, об этом свидетельствуют публикации послед них лет [1][2][3][4][5][6].…”
unclassified
“…Как и для нативного препарата витамина D, несколько ранее опубликованных исследований показали, что пероральный прием кальцитриола после трансплантации почки сни-жает концентрацию в крови ПТГ, улучшает содержание минеральной массы в костях и ассо-циируется с увеличением выживаемости почеч-ных трансплантатов [3,20,47].…”
Section: Review Articles and Lecturesunclassified
“…За последнее десятилетие (пер-вые публикации появились в 2004 г.) накоплен большой опыт наблюдательных исследований, в том числе и собственное клиническое наблюде-ние [54-55], а также опыт длительного лечения цинакальцетом, продемонстрировавшие высо-кую эффективность и безопасность препарата для коррекции гиперкальциемии, гипофосфате-мии и ГПТ у реципиентов почечных трансплан-татов [3,20,47,[54][55][56]. Клиницисты единодушно подчеркивали -коррекция гиперкальциемии и гипофосфатемии, а также снижение содержа-ния в крови ПТГ при лечении цинакальцетом достигаются практически у всех больных, хотя степень этого снижения может сильно варьи-ровать, возможно, из-за своеобразия фармако-кинетики/фармакодинамики препарата и (или) степени гиперплазии и узловой трансформа-ции ОЩЖ [57].…”
Section: Review Articles and Lecturesunclassified